Сутнісна характеристика основних понять категорійного апарату економічного оцінювання відновлення авіаційної техніки - Калиновський, А. О.; Калиновська, Н. Л.; Карабінович, Р. В.; Kalynovskyi, A. O.; Kalynovska, N. L.; Karabinovych, R. V. (Видавництво Львівської політехніки, 2022)
Досліджено сутнісну характеристикк та взаємозв’язок основних понять категорійного апарату економічного оцінювання відновлення авіаційної техніки. Проаналізовано особливості підходу різних авторів до визначення поняття “ремонт авіаційної техніки”. Встановлено, які види ремонтів виконують під час експлуатації авіаційної техніки. Визначено економічні переваги та недоліки застосування різних видів ремонту щодо авіаційної техніки. Проаналізовано чинне законодавство, яке регулює процес виробництва та експлуатації авіаційної техніки в Україні. Встановлено особливості, спільні риси та відмінності між ремонтом авіаційної техніки та її відновленням.

The article is devoted to the study of the essential characteristics and interrelationship of the main concepts of the categorical apparatus of the economic evaluation of the restoration of aviation equipment. Peculiarities of the approach of various authors to the definition of the concept of aircraft repair are analyzed. It has been established what types of repairs are used during the operation of aviation equipment. The economic advantages and disadvantages of using various types of repair for aviation equipment are determined. The current legislation regulating the process of production and operation of aviation equipment in Ukraine is analyzed. Features, common features and differences between aircraft repair and restoration are established. Also, the article examines the peculiarities of the categorical apparatus for the economic assessment of the restoration of aviation equipment. The task of the aviation industry in maintaining the operational condition of aviation equipment has been studied. The main vectors of scientific research related to the repair of aviation equipment have been established. The common views of the authors and points of discussion regarding the content of the concept of “restoration of aviation equipment” are determined. The main stages of aircraft operation and the processes occurring at each stage are defined. The tasks of the performers of works on the restoration of aviation equipment were studied. It was established that a set of measures to ensure the serviceability and efficiency of aviation equipment form a system of technical operation of aviation equipment. In the researched literary sources and regulatory acts, in order to outline these measures, the following terms are usually used: maintenance, repair, restoration, modernization. The purpose of maintenance of aviation equipment is to maintain (preserve) its serviceable or operational condition in accordance with the requirements of regulatory and technical and (or) design documentation. Considering this, definitions that do not allow to set a clear line between maintenance and repair are somewhat incorrect. It was determined that a promising direction of further research is the search for ways to effectively apply the experience, technologies and approaches of foreign aircraft repair enterprises in the conditions of the Ukrainian economy.
The essential characteristics of the basic concepts of the categorical apparatus for the economic assessment of aviation equipment restoration
Keywords: авіаційна техніка; відновлення; ремонт; економічна ефективність; якість; безпека польотів; програма відновлення; aviation equipment; recovery; repair; economic efficiency; quality; flight safety; recovery program; 629.73.083; 338.47-044.3(477)